The customer education playbook : how leading companies engage, convert, and retain customers - Quick, Daniel; Kelly, Barry (Chief Executive Officer) (Ascent Audio, 2022)
Deliver maximum value to customers and clients with this blueprint to customer success In The Customer Education Playbook: How Leading Companies Engage, Convert, and Retain Customers, customer learning experts Barry Kelly and Daniel Quick explain how teaching customers to best engage with your products and services is the key to converting them from prospects to loyal advocates of your brand. In this book, you'll examine how to define success for your customer, create a customer education ₀ the long haul.